'That is when justice becomes complete.' Exemplars' perspectives on forgiveness as a civic virtue in post-genocide Rwanda. Issue 1 (2nd January 2023) - Tirrell, Jonathan M.; Kelly, Erin I.; Gasana, John Gasasira; Dowling, Elizabeth M.; Dennis, Julia; Malvese, Katelyn; Rollman, Elise; Namurinda, Emmanuel; Lerner, Richard M.; Sim, Alistair T. R.
ABSTRACT: Should forgiveness be considered a civic virtue that promotes peace and justice following injustice? In the aftermath of conflicts as severe as state-sponsored genocide, how can relationships be restored, communities reconciled, and justice achieved? We interviewed 15 adults in Rwanda—survivors of the 1994 genocide, nominated as exemplars for their youth-serving roles in their communities and their experiences with forgiving the traumas of the genocide—about their approaches to conflict resolution, their ideas about justice and forgiveness, and their community work. Phenomenological analysis supported considering forgiveness as a civic virtue, as exemplars described a restorative approach to conflict in which justice facilitates, and is completed by, forgiveness. Implications for education emerged from exemplars' accounts, including describing a process of conflict resolution that works toward peace and justice by means of listening, uncovering the truth, acting impartially, encouraging apology and forgiveness, advising for solutions, restoring rights and relationships, and fulfilling justice.